Rufus M. - Estes, Eleanor 1906-1988.; Slobodkin, Louis 1903-1975 (San Diego Harcourt, 2001)
The adventures of seven-year-old Rufus Moffat, living with his widowed mother and older siblings including his encounter with an invisible piano player and his attempts at ventroliquism.
Sequel to: The Middle Moffat.
Sequel to: The Moffat Museum.
"An Odyssey/Harcourt Young Classic"
"Ages 8 and up"--cover p. [4].
Keywords: Brothers and sisters -- Fiction; Family life -- Connecticut -- Fiction; Connecticut -- Fiction